AN INDUCTIVE APPROACH TO TEACHING LANGUAGE LEARNERS GRAMMAR - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
In our Experimental Teaching Methods article, language information is best processed inductively and without translation. The most natural route to second language learning is outside the classroom, and the best example of experiential learning is immersion in the foreign language community.